2005
DOI: 10.1097/01.ajp.0000125267.40304.57
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cost-Effectiveness Study of Trigeminal Neuralgia Surgery

Abstract: This analysis supports the practice of percutaneous surgeries for older patients with medically unresponsive trigeminal neuralgia. At longer follow-up intervals, microvascular decompression is predicted to be the most cost-effective surgery and should be considered the preferred operation for patients if their risk for general anesthesia is acceptable. More data are needed to assess the role that radiosurgery should play in the management of patients with trigeminal neuralgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 43 publications
1
31
0
2
Order By: Relevance
“…[82][83][84][85]84 using hospital data from Belgium, compared MVD, RFT, PBC, and GK, and found comparable rates of 5-and 10-year pain recurrence. However, percutaneous procedures were more cost effective than MVD and GK.…”
Section: Treatment Cost Effectivenessmentioning
confidence: 99%
“…[82][83][84][85]84 using hospital data from Belgium, compared MVD, RFT, PBC, and GK, and found comparable rates of 5-and 10-year pain recurrence. However, percutaneous procedures were more cost effective than MVD and GK.…”
Section: Treatment Cost Effectivenessmentioning
confidence: 99%
“…The two groups of patients are not directly comparable, therefore it is not possible to conclude that CKR is as effective as MVD. CKR group was signifi cantly older than the MVD group, even if age has not been found to be a predictor of success/failure for either radio surgery or MDV procedures (Pollock et al 2005), and patients in MVD group had typically less severe facial pain at baseline. The difference in patients' characteristics is explained by the fact that CKR is not seen as an alternative to MVD for the time being but, rather, as a second line strategy whenever MVD is not possible to deliver.…”
Section: Discussionmentioning
confidence: 88%
“…Even though MVD represents the fi rst choice for those patients (Fujimaki et al 1990;Lee et al 1997;Apfelbaum et al 2000), less invasive procedures such as radiofrequency rhizotomy (Taha et al 1995;Kanpolat et al 2001;Tronnier et al 2001), glycerol rhizotomy (Lundsford et al 1984;Saini 1987;Burchiel 1988;Young 1988;North et al 1990), balloon compression (Brown et al 1993;Skirving et al 2001) and gamma knife stereotactic radio surgery (Kondziolka et al 1996;Rogers et al 2000;Maesawa et al 2001;Pollok et al 2002;Brisman et al 2002) are preferred for elderly patients suffering from signifi cant comorbidities, or with recurrent facial pain after prior surgery (Pollock et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…26 A second study carried out at the Mayo Clinic looked at the cost effectiveness of SRS vs. MVD and found that MVD was more expensive in the near term; but for patients with longer life expectancies, it seemed to be the more cost-effective option. 27 …”
Section: Gkrs For Tnmentioning
confidence: 99%